2017
DOI: 10.1007/s13204-017-0620-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanosilicon dioxide on growth performance, egg quality, liver histopathology and concentration of calcium, phosphorus and silicon in egg, liver and bone in laying quails

Abstract: This experiment was conducted to evaluate the effects of different levels of nanosilicon dioxide (nSiO 2 ) on performance, egg quality, liver histopathology and concentration of calcium (Ca), phosphorus and silicon (Si) in egg, liver and bone in laying quails. The experiment was administered using 60 laying quails at 16-26 weeks of age with five treatments [0 (control), 500, 1000, 2000 and 4000 mg nSiO 2 per kg of diet] and four replicates in a completely randomized design. During the experiment, the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Yeo et al reported the reduced sodium uptake and transpirational bypass flow by Oryza sativa due to treatment with silicon [122]. In the work of Faryadi and Sheikhahmadi, nano-silicon dioxide supplements affected the weights of eggs and increased the bone ash content and calcium in laying quails [123].…”
Section: Nanosilicon Dioxidementioning
confidence: 99%
“…Yeo et al reported the reduced sodium uptake and transpirational bypass flow by Oryza sativa due to treatment with silicon [122]. In the work of Faryadi and Sheikhahmadi, nano-silicon dioxide supplements affected the weights of eggs and increased the bone ash content and calcium in laying quails [123].…”
Section: Nanosilicon Dioxidementioning
confidence: 99%
“…After the exposure of zebrafish eggs to silica NPs, no subsequent occurrence of anomalies in the development of embryos, or signs of cardio-and hepatotoxicity was revealed, although there were some features in behavioral reactions [33]. Feeding female quails with SiO 2 nanoparticles for 10 weeks at a dose of up to 4000 mg per kg of feed did not lead to significant changes in blood plasma biochemical parameters and histopathological changes in the liver, but caused a decrease in the weight of the yolks of eggs and an increase in the thickness of their shells [34]. Based on the data listed, it may be concluded that the oral toxicity of silica nanoparticles is relatively low.…”
Section: Discussionmentioning
confidence: 97%
“…Estradiol induces the synthesis of vitellogenin in the avian liver (Gruber et al, 1976). Reduction synthesis of vitellogenesis could be a reason for the reduced yolk weight and egg weights (Faryadi and Sheikhahmadi 2017). Therefore, it seems probably that decrease in plasma LH level due to the addition of lead acetate to the diet of quails could be a possible reason to reduced egg production and egg mass.…”
Section: Discussionmentioning
confidence: 99%